PENGUATAN STRATEGI KONTEN DIGITAL BAGI UMKM VCO DI BALI: PENINGKATAN KUALITAS VISUAL, NARATIF, DAN ENGAGEMENT MEDIA SOSIAL - Hetty Karunia Tunjungsari; Viella Marchia (Jurnal Serina Abdimas, 2026)
This community service activity aims to optimize visual and narrative content strategies for Micro, Small, and Medium Enterprises (MSMEs) producing Virgin Coconut Oil (VCO) in Bali through social media platforms. The digital era provides a great opportunity for MSMEs to expand their market reach, but many VCO MSMEs in Bali still face challenges in utilizing social media effectively. This service activity is carried out through intensive training and assistance for JB VCO MSMEs in Bali. The methods used include training on the basics of digital marketing, product photography techniques using smartphones, brand storytelling, writing attractive captions, and strategies for using social media platforms such as Instagram and Facebook. The results of the evaluation showed a significant increase in the knowledge and skills of the partners. There was also an improvement in the quality of visual and narrative content on MSME social media accounts, as well as an average increase in engagement rate by 25-40%. Despite the challenges related to digital literacy and post-mentoring consistency, this program has succeeded in equipping JB VCO MSMEs with crucial digital competencies to increase competitiveness. Recommendations are given to MSMEs to consistently implement strategies, to the government for continuous training programs and facilitation of technology access, and to academics for further research. Kegiatan PKM ini bertujuan untuk mengoptimalkan strategi konten visual dan naratif bagi Usaha Mikro, Kecil, dan Menengah (UMKM) penghasil Virgin Coconut Oil (VCO) di Bali melalui platform media sosial. Era digital memberikan peluang besar bagi UMKM untuk memperluas jangkauan pasar, namun banyak UMKM VCO di Bali masih menghadapi tantangan dalam memanfaatkan media sosial secara efektif. Kegiatan pengabdian ini dilaksanakan melalui pelatihan dan pendampingan intensif bagi UMKM JB VCO di Bali. Metode yang digunakan meliputi pelatihan mengenai dasar-dasar pemasaran digital, teknik fotografi produk menggunakan smartphone, storytelling merek, penulisan caption yang menarik, serta strategi penggunaan platform media sosial seperti Instagram dan Facebook. Hasil evaluasi menunjukkan peningkatan signifikan pada pengetahuan dan keterampilan mitra. Terjadi pula peningkatan kualitas konten visual dan naratif pada akun media sosial UMKM, serta peningkatan engagement rate rata-rata sebesar 25-40%. Meskipun terdapat tantangan terkait literasi digital dan konsistensi pasca-pendampingan, program ini berhasil membekali UMKM JB VCO dengan kompetensi digital yang krusial untuk meningkatkan daya saing. Rekomendasi diberikan kepada UMKM untuk konsisten menerapkan strategi, kepada pemerintah untuk program pelatihan berkelanjutan dan fasilitasi akses teknologi, serta kepada akademisi untuk penelitian lanjutan.